Stable isotope‐labelled intravenous microdose for absolute bioavailability and effect of grapefruit juice on ibrutinib in healthy adults. (15th January 2016) - de Vries, Ronald; Smit, Johan W.; Hellemans, Peter; Jiao, James; Murphy, Joseph; Skee, Donna; Snoeys, Jan; Sukbuntherng, Juthamas; Vliegen, Maarten; de Zwart, Loeckie; Mannaert, Erik; de Jong, Jan
Abstract : Aims: Ibrutinib, an inhibitor of Bruton's tyrosine kinase, is used in the treatment of mantle cell lymphoma or chronic lymphocytic leukaemia. Ibrutinib undergoes extensive rapid oxidative metabolism mediated by cytochrome P450 3A both at the level of first pass and clearance, which might result in low oral bioavailability. The present study was designed to investigate the absolute bioavailability (F) of ibrutinib in the fasting and fed state and assess the effect of grapefruit juice (GFJ) on the systemic exposure of ibrutinib in order to determine the fraction escaping the gut (Fg ) and the fraction escaping hepatic extraction (Fh ) in the fed state. Methods: All participants received treatment A [560 mg oral ibrutinib, under fasting conditions], B (560 mg PO ibrutinib, fed, administered after drinking glucose drink) and C (140 mg oral ibrutinib, fed, with intake of GFJ before dosing). A single intravenous (i.v.) dose of 100 μg 13 C6 ‐ibrutinib was administered 2 h after each oral dose. Results: The estimated 'F' for treatments A, B and C was 3.9%, 8.4% and 15.9%, respectively. Fg and Fh in the fed state were 47.0% and 15.9%, respectively. Adverse events were mild to moderate in severity (Grade 1–2) and resolved without sequelae by the end of the study. Conclusion: The absolute oral bioavailability of ibrutinib was low, ranging from 3.9% in the fasting state to 8.4% when administered 30 min before a standard breakfast without GFJ and 15.9% with GFJ. Ibrutinib was well tolerated following a single oral and i.v. dose, under both fasted and fed conditions and regardless of GFJ intake status.